Role of Health Check-Ups in Non-Communicable Diseases’ Detection at Primary Health Care - Nargiza Egamova; Rano Turdievna Sabitova; Yusuf Malikov; Fazliddin Usmanov; Utkir Bakhronov (International Journal of Public Health Science (IJPHS), 2013)
Uzbekistan has been conducting the pioneering health care reform activities for the last 15 years. One of the main aims of the reform was creating accessible and quality primary health care (PHC) services. If in first years of the reform the attention was paid to prevention of infectious diseases and maternal and child health issues currently the focus has shifted to prevention of non-communicable diseases (NCD). While country has building a national stratedy to combat NCD Navoi Regional Health Administration (NOHA) has implemented a study to reveal a true frequence of NCD in region that might be applicable for whole country. The purpose of the research was to conduct basic health check-up at the 4 rural Primary Health Care (PHC) facilities in Navoi region and timely detect non - communicable diseases, with special emphasis on the diabetes mellitus. In general, the quantity of NCD increased for 1012 new (24,6%) cases. According the diabetes mellitus, it was detected that 35 people were registered as “D” category of chronic patients and received appropriate care. In the frame of the health check-up there were 24 new cases detected, the total number of patients with diabetes mellitus is 59 people. This exceeded the available rates of DM in 1,7 times. Our results are comparable with NCD situation in other countries developed and non-developed as well. There was high number of people with hidden forms and higher risks for the DM development. Mass screening of our rural population in the PHC facilities has confirmed that the global DM incidence tendencies are true for our population as wellDOI: http://dx.doi.org/10.11591/ijphs.v2i4.4067